Knowledge, Practices, and Attitudes Towards Silver Diamine Fluoride Therapy Among Dentists and Students in Southeastern Spain - Clara Serna-Muñoz; Marina Lucas-Porras; Yolanda Martínez-Beneyto; Amparo Pérez-Silva; Francisco Javier Ibañez-López; Antonio José Ortiz-Ruiz (Dentistry Journal)
Background/Objectives: The use of silver diamine fluoride (SDF) has increased in recent years for the management of caries lesions in children and adults. The aim of this study is to determine the level of knowledge and the attitude of Spanish dentists (GDPs) and final-year dental students (DSs) regarding the use of SDF. Methods: A cross-sectional survey (questionnaire) was carried out aimed at final-year dental students (DSs) (n = 43) and registered dentists (GDPs) (n = 1050) in the autonomous community of the region of Murcia (Spain). Results: the response rates were GDPs 7.7% (n = 81) and DSs 84.5% (n = 38). Only 20.98% of GDP respondents reported having been trained on SDF versus 100% of DSs. Significant differences were observed between the groups (p < 0.05). While 94.7% of the students were aware of the indications for the use of SDF, only 56.8% of the general dentists reported it. Similarly, for hypersensitivity treatment, 71.1% of the students were informed versus 40.7% of the general dentists, and indications for paediatric patients, 100% for the DS group and 59.3% in GDPs. In adult patients, indications vary from GDPs’ (50%) to DSs’ (25.9%) responses. About 94.7% of DSs know the advantages of use and only 50.6% of GDPs. Both groups showed reluctance to use SDF in esthetic zones, with greater acceptance in non-esthetic areas (p < 0.05). In practice, fewer GDPs (27.16%) and DSs (23.68%) had applied SDF, reflecting a gap between knowledge and implementation. Conclusions: Dental students had a significantly higher level of knowledge, a situation that evidences the high level of education and training in the curricular guides of the universities.